MANAJEMEN STRATEGIS DALAM PENGEMBANGAN PENDIDIKAN ISLAM: KONSEP, IMPLEMENTASI, DAN TANTANGANNYA - Nasuhi; Rika Sa’diyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Strategic management is an organizational management approach oriented toward achieving long-term goals through systematic processes of planning, implementation, and evaluation. In the context of Islamic education, strategic management plays a crucial role in improving educational quality, strengthening institutional competitiveness, and ensuring that all management processes remain aligned with Islamic values. This paper aims to examine the concept of strategic management in the development of Islamic education, explain its implementation stages, and identify the challenges encountered in its application. The study employs a literature review method by analyzing various theories and relevant references related to strategic management and Islamic education. The findings indicate that the implementation of strategic management in Islamic educational institutions involves three main stages: strategy formulation, strategy implementation, and strategy evaluation and control. Effective implementation helps educational institutions determine a clear direction for development, optimize resource utilization, enhance educational service quality, and strengthen organizational accountability. However, its application continues to face various internal and external challenges, including limited human resources, financial constraints, inadequate use of technology, increasing competition among educational institutions, and the impacts of globalization and digital transformation. Therefore, strengthening human resource competencies, maximizing the use of information technology, and fostering an organizational culture based on Islamic values are essential to ensure the effective implementation of strategic management in supporting the sustainable development of Islamic education.